2010
DOI: 10.1063/1.3372726
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed-laser excited thermal lens spectroscopy with sample-fluid heat coupling

Abstract: Analytical and finite element analysis modeling methods of the pulsed-laser excited photothermal (PT) lens signal of solids samples surrounded by air are presented. The analytical and finite element analysis solutions for the temperatures induced in the sample and in the air were found to agree over the range of conditions in this report. Model results show that the air contribution to the total PT lens signal is significant in many cases. In fact, these solutions open up the possibility of applying the pulsed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The two beams have no delay when they reach PBS1 except for the acoustic vibration induced phase difference, and they finally interfere after being converted to circular polarization states with a fiber polarization controller. The beams are split one last time with PBS3 to dramatically reduce interferometer noise and make the system insensitive to thermal lens [25] effects induced by the pumping laser. When the polarization controller (PBS3 in the drawing) is tuned to act as a perfect quarter wave plate, the two beams have opposite signs in the interference term at the two inputs of a balanced photodetector.…”
Section: Methodsmentioning
confidence: 99%
“…The two beams have no delay when they reach PBS1 except for the acoustic vibration induced phase difference, and they finally interfere after being converted to circular polarization states with a fiber polarization controller. The beams are split one last time with PBS3 to dramatically reduce interferometer noise and make the system insensitive to thermal lens [25] effects induced by the pumping laser. When the polarization controller (PBS3 in the drawing) is tuned to act as a perfect quarter wave plate, the two beams have opposite signs in the interference term at the two inputs of a balanced photodetector.…”
Section: Methodsmentioning
confidence: 99%
“…The latter is a good approximation when air is the surrounding fluid. 19 The initial temperature change is assumed to be zero, T ( r , z, 0 ) = 0. Here Q 0 = 2 E 0 A e (1 – R )φ/ c ρπω 2 0 e , E 0 is the pulse laser energy, A e is the optical absorption coefficient at the excitation beam wavelength, R is the surface reflectivity, and ω 0 e is the electric field beam waist radius parameter.…”
Section: Theorymentioning
confidence: 99%
“…Recently, we have shown that TL and TM spectroscopies can be used to study the sample-fluid heat-coupling problem in the case of low-optical-absorbing material by using continuous 12 or pulsed excitation. 13 Similar to the mirage method, the TM technique can be used to (1) determine thermal and optical proprieties of transparent fluids by using a reference solid material as absorber medium, and (2) determine thermal and mechanics proprieties of solid material, knowing the transparent fluids.…”
Section: Introductionmentioning
confidence: 99%